Intersectionality and intelligibility: queer worldmaking in body positivity and fat activism - Otis, Hailey, author; Dunn, Thomas R., advisor; Gibson, Katie, committee member; Cloud, Doug, committee member (Colorado State University. Libraries, 2017)
This thesis analyzes queer rhetoric produced by fat activists Tess Holliday and Ashleigh Shackelford to understand the larger worldmaking projects of body positivity and fat activism. This thesis uses perspectives and assumptions from the fields of queer theory, fat studies, and rhetoric to construct a queer critical framework and orientation for analyzing and understanding the rhetorical strategies employed by these rhetors. Not only does this thesis perform close readings of texts produced by both Holliday and Shackelford to understand and illuminate the queer worlds they rhetorically construct, it uses queer rhetorical criticism to take part in the larger worldmaking project of fat activism from the position of the critic. After performing queer rhetorical criticism on texts produced by Holliday and Shackelford, this thesis explores in theoretical depth the queer worlds created by these rhetors' fat activist rhetoric. After exploring their individual queer worlds, this thesis puts these two rhetors in conversation with one another to understand the larger queer worldmaking project of fat activism, particularly the role intersectionality plays in constituting political subjects of body positivity. The conclusion of this thesis cogitates on the implications of this project for theory and scholarship, for understanding the particulars of queer worldmaking, and for activism on a practical level. Ultimately, this thesis makes a strong case for the importance, the necessity, of intersectionality in queer rhetorical scholarship, the body positivity movement, and activism broadly.
Keywords: fat activism; intersectionality; worldmaking; fat studies; body positivity; queer theory